To Be A Father In Biutiful Movie (2011) Directed By Alejandro González Iñárritu Existentialist Approach - Jannah, Ana Rodhotul (2012)
The object of study is Biutiful movie by Alejandro González Iñárritu. It usesexistentialist approach. In analyzingthis movie, the writer uses qualitative and existentialist approach. The Primary data source of this research is BiutifulMovie by Alejandro González Iñárrituand synopsis of Biutiful movie. The secondary data sources are the author's biography, essay, comment, homepage, and website about the movie and other relevant sources. The study comes to the following conclusions. First,based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound and editing are related to each other and form a unity. Second based on the existentialist analysis there are aspects of existentialism, namely; being, existence before essence, consciousness, freedom to choose, anxiety, transcendence of ego and nothingness in the struggle of Uxbal in making balance between serving his family and fighting to get his dreams of life.